Laboratórios do Departamento de Ciências Básicas - Casatti, Cláudio Aparecido; Castro, João César Bedran de; Piedade, André Luis Mattos; Baiochi, Ângelo Luiz; Santos, Arnaldo César dos; Junqueira, José Ari Gualberto; Alberto, Mauro; Pinheiro, Sandra Aparecida dos Santos (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação Ângelo Luiz Baiochi José Ari Gualberto Junqueira Sandra Aparecida dos Santos Pinheiro